Understanding the relationship between mode and destination choices for personal out-of-town travel. (April 2023) - Aultman-Hall, Lisa; Onayev, Anuarbek; Dowds, Jonathan; LaMondia, Jeffrey J.
Highlights: Bundled decision-making of mode and destination was confirmed using a random representative population sample. Choices are influenced by mode-specific travel times, distance, and whether they were part of a bundled decision. Out-of-town model structures require more complex predictors in addition to distance. Abstract: In post-COVID era, more agencies will seek to incorporate long-distance or overnight travel into their travel forecasting. This paper leverages a unique survey dataset (n = 440) that queried participants' propensity to make simultaneous or bundled decisions on mode and destination location for their most recent overnight out-of-town personal trip. The random representative sample of Vermont residents indicated they mostly make bundled decisions of destination and mode choice. Binary logistic regressions were estimated to determine (a) sociodemographic factors (e.g. age, income) and trip travel distance influence the likelihood an individual will bundle their mode and destination choice and (b) mode-specific travel times, distances traveled and bundled decisions influence mode choices. Results validate that out-of-town travel destination and mode decisions are sometimes integrated, and different populations treat this decision process differently. Moreover, choice models of this behavior require more complex predictors in addition to distance, including whether it is part of a bundled decision.